Kesehatan Mental dan Spiritualitas Remaja Muslim: Analisis Hadis tentang Ketentraman Jiwa di Era Digital - Muhammad Ihsan Mas'ud; Nasrulloh (Al-Kindi, 2026)
The rising psychological strain experienced by Muslim adolescents in the digital age is closely tied to the increasingly intensive use of social media, which leads to information overload, tendencies toward self-comparison, and mental fatigue. This study aims to describe the mental health conditions of Muslim youth and connect them with prophetic teachings on inner tranquility, particularly the concepts of dhikr, tawakkul, and balanced living. Using a qualitative-descriptive approach and textual analysis of religious sources, the data were gathered through a literature review of relevant hadiths, classical and contemporary scholarly commentaries, and modern psychological findings. The analysis reveals that adolescents often experience digital anxiety, emotional instability, identity-formation pressures, and diminished inner calm due to excessive digital exposure. The integrative discussion highlights that hadith-based values provide a spiritual foundation for restoring mental balance, including strengthening one’s relationship with God, practicing dhikr as a means of emotional regulation, applying tawakkul in facing life’s pressures, and avoiding extreme behaviors. The study emphasizes that prophetic teachings can serve as a basis for developing psycho-spiritual resilience and self-regulation strategies relevant to Muslim adolescents amid modern challenges. The implications point to the importance of incorporating religious values into youth mental health programs, family education, and spiritual guidance within educational and religious institutions. Keywords: Mental Health, Muslim Adolescents, Digital Era, Hadith on Inner Tranquility, Spirituality.